2014
DOI: 10.3233/nre-141094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galvanic vestibular stimulation combined with physical therapy on pusher behavior in stroke patients: A case series

Abstract: BACKGROUND: A recent study investigated the effects of galvanic vestibular stimulation (GVS) on pusher behavior (PB) in post-stroke patients. However, there have been no reports about the effects of multisession GVS on PB. OBJECTIVE: The purpose of this study was to investigate the feasibility and effects of multisession GVS combined with physical therapy for PB in stroke patients. METHODS: Two stroke patients who showed PB were enrolled. The ABAB single-case design was used. Each phase lasted 1 wk. In phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Thus, presenting an inclined view that emphasizes the inclination of the vertical axis that the patients are aware of might be able to increase the degree of difficulty of the balance exercises to an appropriate level. Moreover, if the presented tilted view is combined with vibration and vestibular stimuli, the training effect may be increased further 10 , 11 , 12 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, presenting an inclined view that emphasizes the inclination of the vertical axis that the patients are aware of might be able to increase the degree of difficulty of the balance exercises to an appropriate level. Moreover, if the presented tilted view is combined with vibration and vestibular stimuli, the training effect may be increased further 10 , 11 , 12 ) .…”
Section: Discussionmentioning
confidence: 99%
“…These disorders might be treated by intervention with sensory input. Although there are previous studies about the change in standing posture due to vibration stimulation and/or vestibular stimulation 10 , 11 , 12 ) , there are few studies about the role of visual intervention in standing posture. Prism glasses can bias a view on sagittal and/or horizontal planes, but cannot shift it on coronal plane 13 , 14 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Selectively influencing this area via enhanced proprioceptive input of muscle spindles via exercise may be indicated. Some researchers have incorporated galvanic stimulation for patients with lateropulsion 11,12,34 as a way to modulate input to the network of brain centers responsible for the egocentric postural reference system for vertical upright. Based on the current findings implicating the inferior parietal lobe, one may speculate that modulating the activity of the inferior parietal cortex via transcranial direct current stimulation or transcranial magnetic stimulation may also provide a rational therapeutic strategy to test as a potential intervention for lateropulsion.…”
Section: Lesion Sizementioning
confidence: 99%
“…7 Patients with lateropulsion have delayed functional recovery, 3,8 especially when right-sided brain lesions are present. 9,10 Novel strategies, 11,12 such as transcranial neuromodulation techniques, could augment functional recovery, but these approaches are most likely to be effective if guided by neuroanatomical mechanisms underlying lateropulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura et al [26] confirmed that pusher behavior was reduced by applying galvanic vestibular stimulation to stroke patients with pusher behavior. As a result, the improvement in weight distribution of the left and right legs positively affected walking.…”
Section: ⅳ Discussionmentioning
confidence: 94%